Protection of Customary Communities in Compensation for Losses on Common Land Objects for Public Interest (Study of Sorong District Court Decision Number: 120/Pdt.G/2018/PN.Son) - Putri, Nasywa Awalia; Winanti, Atik (Dinasti Research, 2025)
Customary law communities have a strong connection to natural resources and customary land as their main source of livelihood. This study was conducted to determine the protection of customary law communities on customary land for the public interest, as well as the judge's considerations in Decision No. 120/Pdt.G/2018/PN.Son regarding compensation for customary land. The researcher applied a normative juridical method through a Statute Approach and a Case Approach in analyzing the topic or issue. The results of the study show that protection is provided in the form of preventive and repressive actions by the government. Preventive efforts are carried out by forming Law No. 12 of 2012 and its derivative regulations to prevent disputes and guarantee the rights of customary law communities in land acquisition. Repressive efforts are pursued through the settlement of disputes in court by filing lawsuits in accordance with the provisions of the law. In Decision No. 120/Pdt.G/2018/PN.Son, the judge can use three stages, namely constatation, qualification, and constitution, to reach a good decision based on the principle of justice. Compensation in this decision was awarded as recognition and respect for the Marga Momo Indigenous Community. This writing is expected to demonstrate the importance of balancing development for the public interest and the protection of the rights of indigenous peoples with laws that favor justice.